Experimental Study on the Mechanical Properties of Porcine Cartilage with Microdefect under Rolling Load. (12th June 2017) - Men, Yu-tao; Li, Xiao-ming; Chen, Ling; Fu, Hu
Abstract : Objectives . To investigate the mechanical responses of microdefect articular cartilage under rolling load and find out the failure rule. Methods . Rolling load was applied to the porcine articular cartilage samples with rectangular notches of different depths. The displacement and strain near the notches were obtained by the noncontact digital image correlation technique. Results . The strain value and peak frequency around the notch increased; the maximum equivalent strain value could be observed at both bottom corners of the notch; the equivalent strain value first increased and then decreased at the points in the superficial and middle layers with the increase of rolling velocity; the points in the deep layer were less affected by rolling velocity; the equivalent strain value of the points in the superficial layer declined after rising with the increase of defect depth, while a decreased trend could be found for the points in the middle and deep layers. Conclusions . The shear strain, which rose with the increase in defect depth, was the main factor in cartilage destruction. The cartilage tended to be destructed firstly at the bottom corner of the defect. Rolling velocity showed significant effects on superficial and middle layers. Cartilage had the ability to resist destruction.